The Influence of Disaster Preparedness Bag Video Media on Earthquake Preparedness - Tria Nopi Herdiani; Rifda Neni; Ida Nurani (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2025)
RT 08 Jenggalu, the only RT in Jenggalu and located on the coast, faces a high risk of earthquakes. From a survey on December 29, 2023 and an interview on January 18, 2024, among 190 families, one person knew about the disaster preparedness bag, five people did not understand, and two people knew but did not understand the contents.This study aims to study the effect of disaster preparedness bag video media on earthquake disaster preparedness in RT 08 Jenggalu. This type of research uses pre-experimental using a one group pretest - posttest design. The population of this study was the community of RT 08 Jenggalu with a total of 190 families, the sample in this study was 65 people..Sampling collection technique using purposive sampling. Data collection techniques with primary data and secondary data. Data analysis with normality test, univariate analysis andWilcoxon Signed Rank Test.The research results were obtainedFrom 65 respondents before being given the disaster preparedness bag video material, 24 respondents had high preparedness, 22 respondents had moderate preparedness and 19 respondents had low preparedness. After being given the disaster preparedness bag video material, 57 respondents had high preparedness and 8 respondents had moderate preparedness. There was a difference in knowledge about earthquake disaster preparedness in the community of RT. 08 Jenggalu before and after being given the disaster preparedness bag video material with a p-value = 0.000 <0.05, meaning significant.